Genome-wide identification and characterization of soybean GH9 endo-1,4-β-glucanases - Zhan, Weimin; Huang, Huijuan; Cai, Zaipan; Zhao, Zhenwei; Lin, Xuefu; Peng, Yize; Dong, Zhicheng; Qin, Di; Jiang, Li (Frontiers in Plant Science, 2025)
Cellulases are a crucial class of enzymes involved in cellulose synthesis and metabolism, significantly contributing to plant growth, development, and organ abscission. The role of Glycosyl hydrolase family 9 (GH9), a major gene family encoding cellulase, remains poorly elucidated in soybean. In this experiment, we identified 43 non-redundant GmGH9 genes in soybean through systematic genome-wide analysis. The physicochemical properties of GmGH9 proteins exhibit variability. Phylogenetic investigations revealed that class B constitutes the predominant evolutionary branch. The GmGH9B/C members display complex splicing patterns. GmGH9As contain typical transmembrane structural domains, while GmGH9Cs uniquely includes the carbohydrate-binding module 49 (CBM49) and signal peptide. Furthermore, we identified 13 distinct types of functional motifs, with light-responsive elements being predominant. Expression profiling of the GmGH9s in soybean revealed spatiotemporal and stress-regulated dynamics across organs, ethylene treatments, and photoperiodic conditions, especially for GmGH9A9 and GmGH9B19. Multi-species collinearity analysis of GH9 genes suggested that GmGH9A2 and GmGH9C4 exhibited greater conservation in pea, tomato, and soybean, which are distinguished by fruit abscission. Additional correlations between the haplotypes of GmGH9A2 and GmGH9C4 and yield-related traits indicated that soybean experienced selected pressure during domestication, resulting in a reduction in their genetic diversity.